2021
DOI: 10.1038/s41577-021-00618-8
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune detection of lipid oxidation as a threat assessment strategy

Abstract: Oxidized phospholipids that result from tissue injury operate as immunomodulatory signals that, depending on the context, lead to proinflammatory or anti-inflammatory responses. In this Perspective, we posit that cells of the innate immune system use the presence of oxidized lipids as a generic indicator of threat to the host. Similarly to how pathogen-associated molecular patterns represent general indicators of microbial encounters, oxidized lipids may be the most common molecular feature of an injured tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 106 publications
(161 reference statements)
2
53
0
Order By: Relevance
“…A direct effect of NO can lead to inhibition of viruses, and in fact, NO is considered one of the earliest antiviral responses of the host [41], whereas indirect effects include the regulation of inflammation and immune response [42]. NO also plays a key role in the generation of oxidized phospholipids [43], which can operate as potent immunomodulatory signals [44]. NO is necessary for the formation of several reactive oxygen and nitrogen species, including peryoxynitrite, dinitrogen trioxide, and nitrogen dioxide, which all can have an antiviral effect.…”
Section: No: Friend or Foe?mentioning
confidence: 99%
“…A direct effect of NO can lead to inhibition of viruses, and in fact, NO is considered one of the earliest antiviral responses of the host [41], whereas indirect effects include the regulation of inflammation and immune response [42]. NO also plays a key role in the generation of oxidized phospholipids [43], which can operate as potent immunomodulatory signals [44]. NO is necessary for the formation of several reactive oxygen and nitrogen species, including peryoxynitrite, dinitrogen trioxide, and nitrogen dioxide, which all can have an antiviral effect.…”
Section: No: Friend or Foe?mentioning
confidence: 99%
“…Reduced in IBD (293,297) Increased in IBS (248,302) Increased in UC (252) and in CD (293) Reduced in CD (252,298) Increased in Parkinson's disease (259) Increased in Alzheimer's disease (300) Decreased in autism spectrum disorder (301) Decreased in bipolar disorder (258) Increases 5-HT levels (232) Correlated with levels of serotonin (303) Veillonellaceae Increased in IBS (304,305) Increased in IBD (305,306) Increased in UC and CD (252) Decreased in autism spectrum disorder (256) Correlated with increased levels of serotonin (307) Lactobacillaceae Increased in IBS (248) Increased in IBD (297) Decreased in IBD (Lactobacillus) (250) Increased in CD and reduced in UC (252) Increased in Parkinson's disease (253,255,308) Decreased in Alzheimer's disease (251) Increased in Alzheimer's disease (300) Increased in autism spectrum disorder (257) Decreases TPH1, 5-THR 3 and 5-HTR 4 expression; and increases SERT expression…”
Section: Ruminococcaceaementioning
confidence: 99%
“…Decreased in Parkinson's disease (259) Increased in autism spectrum disorder (256,257) Correlated with levels of serotonin (303) Prevotellaceae Decreased in IBS (248) Increased in IBS (304) Increased in IBD (326) Increased in UC and CD (252) Decreased in Parkinson's disease (254,327) Decreased in autism spectrum disorder (256,321) Proteobacteria Enterobacteriaceae Increased in IBS (302) Increased in IBD (292,306) Increased in UC and CD (252) Increased in Parkinson's disease (328) Increased in Alzheimer's disease (300) Increased in autism spectrum disorder (257) Decreases 5-HT and SERT protein (329) Increase 5-HT bioavailability (330) Increases EC cells (331) Serotonin-producing bacterial strains (Escherichia coli K-12) insufficient, and novel studies have indicated that more treatments addressing innate immunity should be carried out. In this context, several studies have indicated that TLR (353) and NLR (354) modulation may help in the treatment of these chronic pathologies.…”
Section: Ruminococcaceaementioning
confidence: 99%
“…Oxidized lipids have been shown to accumulate in apoptotic cells as well as microsomes released by activated or dying cells, and are generally associated with inflammatory responses, mediated mainly via the innate immune system 2 . Inflammation modulating potential of oxidized lipids is attributed to their recognition by and thus activation of a wide range of pattern recognition receptors including macrophage scavenger receptors, Toll-like receptors, CD36, and C reactive protein 9 . Moreover, oxidized lipids and their protein adducts can be recognized by natural IgM antibodies and thus sequestered from the circulation 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Both enzymatic (via action of lipoxygenase, and cytochrome P450 systems 11,12 ) and non-enzymatic (via free radical driven lipid peroxidation 13,14 ) systems are proposed to contribute to the accumulation of oxidized lipids. Overall, an increasing body of evidence allows to propose that action of oxidized complex lipids is context dependent and their bioactivities might be manifested either in adaptive or pathological manner 9,11 . Understanding the underlying regularities in epilipidomics patterns would require holistic mapping of oxidized lipids in different conditions in a variety of biological matrices.…”
Section: Introductionmentioning
confidence: 99%